Obstacles of using the science lab from the point of view of the science teachers of the high basic stag in Mafraq directorate - Al- shregee, Suhaila Suleiman (Journal of Educational and Psychological Sciences, 2019)
The study was designed to identify the obstacles of using the science lab from the point of view of the science teachers of the high basic stage in Al- Mafraq directorate. The study followed the descriptive method and the questionnaire was applied as a data collection tool. The study community was formed from all teachers of science for the high primary stage in the province of Mafraq during the first semester 2018/2019, The sample of the study was randomly selected by 40% of the original study population. The results showed that the obstacles of using the science lab came in a medium degree from the point of view of the sample of the study and there were no statistically significant differences at the significance level of 0.05 = α attributable to the type or qualification or years of experience. And the study recommended the provision of schools by laboratories that suit the numbers of students in the schools, the need to provide the laboratory with specialized teacher in each school laboratory, to provide the school laboratories with the appropriate tools and methods for the science curriculum, periodic maintenance of laboratories, training of teachers on scientific experiments and safety procedures and general maintenance in the laboratory